Community Organizations Behaving Badly: An Examination of Citizen Participation and Learning in and Through Community Building Activities - Hleziphi Naomie Nyanungo (Adult Education Research Conference, 2007)
The paper presents findings from a critical ethnographic study that examined how the behavior of community organizations shaped participation and learning of community residents engaged in community building activities.